Deciphering the pH-dependence of ground- and excited-state equilibria of thienoguanine. Issue 14 (25th March 2020) - Didier, Pascal; Kuchlyan, Jagannath; Martinez-Fernandez, Lara; Gosset, Pauline; Léonard, Jérémie; Tor, Yitzhak; Improta, Roberto; Mély, Yves
Abstract : Proposed photophysics of th Gb under acidic conditions. Abstract : The thienoguanine nucleobase ( th Gb ) is an isomorphic fluorescent analogue of guanine. In aqueous buffer at neutral pH, th Gb exists as a mixture of two ground-state H1 and H3 keto–amino tautomers with distinct absorption and emission spectra and high quantum yield. In this work, we performed the first systematic photophysical characterization of th Gb as a function of pH (2 to 12). Steady-state and time-resolved fluorescence spectroscopies, supplemented with theoretical calculations, enabled us to identify three additional th Gb forms, resulting from pH-dependent ground-state and excited-state reactions. Moreover, a thorough analysis allowed us to retrieve their individual absorption and emission spectra as well as the equilibrium constants which govern their interconversion. From these data, the complete photoluminescence pathway of th Gb in aqueous solution and its dependence as a function of pH was deduced. As the identified forms differ by their spectra and fluorescence lifetime, th Gb could be used as a probe for sensing local pH changes under acidic conditions.